Delamination phenomena in aluminum/polyimide deformable interconnects: In-situ micro-tensile testing. (5th January 2016) - Lucchini, Riccardo; Cattarinuzzi, Emanuele; Maraghechi, Siavash; Gastaldi, Dario; Adami, Andrea; Lorenzelli, Leandro; Vena, Pasquale
Abstract: The deformation and failure mechanisms of metal/polymer electrical interconnects with S-shaped planar meanders are investigated. Samples consist of 1 μm thick aluminum conductive coating evaporated on a 10 μm thick polyimide substrate. Uniaxial tensile tests up to 40% stretch with in-situ optical and scanning electron microscopy (SEM) were performed to assess the effects of different meander geometries on the local mechanics. As a consequence of the large strain experienced by the underlying polymeric substrate, two different delamination modes were observed at the metal/polymer interface, namely, (a) shear-based and (b) buckling-based delamination. Mechanisms (a) and (b) are activated depending on the specific meander geometry: interestingly, a crucial role was played by the length of rectilinear arms, which was shown to influence the extent of transverse contraction experienced by the interconnect. Upon increasing stretch, in-situ SEM observations revealed detrimental effects related to the interfacial failure, as metal fracture localizes in the delaminated areas. Experimental results suggest that, in addition to the need of surface treatments aimed at improving the metal/polymer interface adhesion, it is also crucial to conceive optimal geometrical designs to achieve mechanical reliability of stretchable interconnects. Graphical abstract: Highlights: In-situ mechanical testing: mechanical reliability of metal/polymer systems for deformable electronics Serpentine shaped thin metal aluminum conductive lines on polyimide substrates are investigated. Two deformation mechanisms are identified: a) shear-based and b) buckling-based delamination. The crucial role of the geometrical features of the serpentine design is assessed.